2016
DOI: 10.1111/1348-0421.12356
|View full text |Cite
|
Sign up to set email alerts
|

The bvg‐repressed gene brtA, encoding biofilm‐associated surface adhesin, is expressed during host infection by Bordetella bronchiseptica

Abstract: Bordetella species display phase modulation between Bvg þ and Bvg À phases. Because expression of known virulence factors is up-regulated in the Bvg þ phase, bacteria in this phase are considered competent for infection. However, the Bvg À phase is of negligible importance for infection. No studies have shown that bacterial factors specific to the Bvg À phase (bvg-repressed factors) are expressed in the course of Bordetella infection. In the present study, the gene brtA (Bordetella RTX-family Adhesin), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…Here we confirm the role for the Bvg-regulated adhesin BrtA, a putative homolog of the well-characterized LapA adhesin of Pseudomonas fluorescens , in biofilm formation by B . bronchiseptica , as has recently been reported by Nishikawa and colleagues [ 16 ]. Furthermore, we show that the c-di-GMP receptor LapD and the LapD-regulated protease LapG also participate in biofilm formation by B .…”
Section: Introductionsupporting
confidence: 73%
“…Here we confirm the role for the Bvg-regulated adhesin BrtA, a putative homolog of the well-characterized LapA adhesin of Pseudomonas fluorescens , in biofilm formation by B . bronchiseptica , as has recently been reported by Nishikawa and colleagues [ 16 ]. Furthermore, we show that the c-di-GMP receptor LapD and the LapD-regulated protease LapG also participate in biofilm formation by B .…”
Section: Introductionsupporting
confidence: 73%
“…Strain CVO also increased expression of a type I secretion system and a gene for an RTX‐related protein, both gene products potentially involved in adhesion. RTX protein VCBS‐repeat and cadherin‐like domains have been shown to mediate binding to abiotic surfaces (Hinsa et al ., ; Nishikawa et al ., ). The domain structure of the RTX‐type protein in strain CVO and its elevated gene expression during S 0 oxidation suggest it could play a role in surface attachment.…”
Section: Discussionmentioning
confidence: 97%
“…However, recent studies indicate that Bordetella cells do experience Bvg2 conditions in vivo (Mason et al, 2013;Hoo et al, 2014, Dewan et al, 2017. In another study, investigators identified B. bronchiseptica brtA, a lapA ortholog, and demonstrated it was a Bvg2 phase gene involved in biofilm formation and expressed in infected rat trachea (Nishikawa et al, 2016). Although we could find no reports of the concentrations of Na in a mammalian respiratory tract, eukaryotic cells have cycling pathways that excrete pyridines and NAD breakdown products for later use in NAD synthesis (Nikiforov et al, 2015), so it is reasonable to hypothesize that Na may be present extracellularly in the host.…”
Section: Discussionmentioning
confidence: 99%